Narrow band imaging versus white light for detecting sessile serrated lesion: A prospective randomized multicenter study. Issue 1 (1st September 2021) - Staudenmann, Dominic; Liu, Ken; Varma, Poornima; Wong, May; Rai, Sonam; Tsoutsman, Tatiana; Choi, Kyung Ho; Saxena, Payal; Kaffes, Arthur John
Abstract: Objectives: Colonoscopy is the gold standard diagnostic test used to detect early colorectal lesions and prevent colorectal carcinoma. Narrow band imaging (NBI) is an imaging technique that provides improved image resolution of the mucosa during endoscopy. Whether NBI improves the detection of sessile serrated lesion (SSL) is controversial—our aim was to assess this during routine colonoscopy. Methods: We conducted a multicenter, prospective, randomized, controlled trial. Patients underwent colonoscopy for screening, surveillance, or symptoms. They were randomized to either high‐definition white light (HD‐WL) or NBI in a 1:1 ratio. The primary outcome was SSL detection rate. Secondary outcomes were adenoma detection rate (ADR) and polyp detection rate (PDR). Results: A total of 400 patients were randomized to NBI (N = 200) or HD‐WL (N = 200). The total colonoscopy time was slightly longer in the NBI group compared to HD‐WL (median time 14 vs. 12 min, p = 0.033). There were no statistically significant differences in SSL detection rate (7.5% NBI vs. 8.0% HD‐WL; p = 0.852), ADR (41.0% NBI vs. 37.5% HD‐WL; p = 0.531), or PDR (61.0% NBI vs. 54.0% HD‐WL; p = 0.157) between the two groups. No significant predictors of SSL detection were found on univariable or multivariable analysis. Increasing age and increased withdrawal time were an independent predictors of polyp detection and increasing age was also an independent predictor of adenoma detection on multivariable analysis. Conclusion: In the hands of experienced colonoscopists, NBI does not improve SSL detection compared to HD‐WL. Withdrawal time and patient age remain important factors for polyp and adenoma detection.